2021
DOI: 10.1016/j.jaad.2021.02.032
|View full text |Cite
|
Sign up to set email alerts
|

How telemedicine may exacerbate disparities in patients with limited English proficiency

Abstract: How telemedicine may exacerbate disparities in patients with limited English proficiency Type of communication Barriers Proposed best practices Written communication Telemedicine has led to increased use of written communication. The default language for online medical record, emails, instructions for storeand-forward photo-taking and uploading, and text messages is English. Adapt all forms of written communication to patient preferred language Varying levels of written literacy Consider visual tutorials such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…We urge providers to preidentify and address the barriers to adoption rather than confront them after implementation, to ensure a positive experience and service sustainability. 3,4 Extending Linggonegoro et al, 1 we identified the importance of social and cultural norms in the design of telemedicine solutions. 1,5 Sensitivity to these factors is particularly important when deploying teledermatology in heterogeneous populations.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…We urge providers to preidentify and address the barriers to adoption rather than confront them after implementation, to ensure a positive experience and service sustainability. 3,4 Extending Linggonegoro et al, 1 we identified the importance of social and cultural norms in the design of telemedicine solutions. 1,5 Sensitivity to these factors is particularly important when deploying teledermatology in heterogeneous populations.…”
mentioning
confidence: 75%
“…3,4 Extending Linggonegoro et al, 1 we identified the importance of social and cultural norms in the design of telemedicine solutions. 1,5 Sensitivity to these factors is particularly important when deploying teledermatology in heterogeneous populations. We also identified modifiable factors influencing uptake, such as the perceived quality and security of the technology and practical benefits, such as convenience and social distancing.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Additionally, we observed high engagement with the HMP from both English and Spanish speakers. It is well-documented that non-English speaking populations are at risk for significant disparities in the delivery of telemedicine-based care [ 36 38 ]. This data demonstrates that telemedicine programs that are offered in multiple language and are designed with interpretive services as a centerpiece of their care can help overcome these disparities and achieve high engagement and satisfaction among non-English speakers.…”
Section: Discussionmentioning
confidence: 99%